Special Drawing Right and Currency Risk Management - Hassanain, khalifa (International Journal of Economics and Financial Issues, 2015)
SDR valuation is done in terms of currency amounts of the four international reserve currencies, namely the US dollar, the euro, the Japanese yen and the pound sterling. Currencies included in the SDR calculations are determined on the basis of the value of export of goods and services over the past five years. The IMF Rule O-2(a) defines the value of the U.S. dollar in terms of the SDR as the reciprocal of the sum of the equivalents in U.S. dollars of the amounts of the currencies in the SDR basket. Each U.S. dollar equivalent is calculated on the basis of the middle rate between the buying and selling exchange rates at noon in the London market, or New York market or on the basis of euro reference rates published by the European Central Bank depending upon availability. For other currencies, SDR rates are based on SDR-USD rate and USD-other currency rate. Currency rates in terms of USD as reported by the issuing central banks is different from the SDR-USD rate based on London market, this difference cause the SDR to have different dollar values. It can potentially create spurious translation movements, even for a perfectly hedged position. In this study, we assess the impact of different exchange rate quotations for SDR calculations on SDR as a unit of account. Specifically we look at the long run behavior and the short run dynamics of the difference between SDR as done by the IMF and on basis of London market and look at the implications for SDR as a unit of account and for currency risk management for MDBs that currently use SDR as a unit of account. Keywords: SDR, Currency Risk, MDBs JEL Classification: F13, F31, F33, G32